Motion Sickness: Holding the Acupressure Point of Village-Owned Business Entities on the Wheel of “Good Corporate Governance” - Dewi, Amelia Sri Kusuma; prasetyo, Ngesti Dwi; Rifan, Mohamad; Habsari, Hanugrah Titi (Brawijaya Law Journal, 2024)
The transcription of Good Corporate Governance (GCG) scenarios in various state regulations basically attempts to build plots to move various economic resources from an area with low productivity to an area with higher productivity with greater results. However, this condition is different when the Indonesian Government wants Village-Owned Enterprises (BUMDes) which normatively and culturally are not designed for entrepreneurship like BUMD/BUMN. The consequence of this desire is that in its implementation BUMDes tends to be neglected and not bound by the principles of Good Corporate Governance (GCG). Through juridical-normative research methods and 3 (three) legal approaches, this research focuses on "Motion Sickness" towards BUMDes resulting from their placement in the "return on investment" space without Good Corporate Governance (GCG). The results of this research show that when analogous to a vehicle, BUMDes experience Motion Sickness or nausea due to: First, the psychological burden on the apparatus in the Village Government; Second, the Good Corporate Governance (GCG) Design is not in accordance with the BUMDes Design. Hence, the acupressure points that need to be pressed in dealing with BUMDes problems include: legal revitalization in the Village Law, overcoming work culture (such as fraud and insider transactions), sterilization of political elements (separating the interests of village officials from interests of Business Entities), and expansion of the business environment. So that in the future Corporate Governance and Corporate Management in BUMDes can be realized through the commitment of stakeholders such as: Capital Owners/GMS, Board of Supervisory/Commissioners, and Board of Directors.